An Empirical Study of Principals' Leadership Styles with Faculty Commitment - Thanh Hai Nguyen; Quang Nguyen Van; Mai Nguyen Thị Tuyet (Emerging Science Journal, 2022)
Objectives: The objectives of this study were to explore the leadership styles of political school principals and the influence of leadership styles on faculty committees, as well as the influence of leadership styles on faculty-directed demographic variables. Methods/Analysis: This study uses a quantitative method to identify the leadership styles that exist in principals of political schools. The collected data is analyzed and processed in the Statistical Package for Social Sciences (SPSS) version 26.0. The available test of Avolio and Bass to explore leadership styles, the test developed by Meyer and Allen is used to measure faculty commitment. Findings: Transformative leadership styles, transactional leadership styles, and laissez-faire leadership styles all have statistically significant positive correlations with faculty commitment. Novelty/Improvement: The laissez-faire leadership style had the strongest influence on faculty commitment, followed by the transformational leadership style. The least influential leadership style was the transactional leadership style. When lecturers have confidence and initiative, being able to make their own decisions and implement them, they will be more creative to achieve leadership performance. The research results are only shown within the provincial political schools of Vietnam. Future studies may select a broader sample of subjects in many educational institutions of a different kind. Doi: 10.28991/ESJ-2022-06-03-013 Full Text: PDF